Investigation of genetic determinants of drug response in a Plasmodium falciparum genetic cross using a high-throughput screening method - Krause, M (2015)
The emergence and rapid spread of artemisinin-resistant Plasmodium falciparum in southeast Asia highlights the importance of identifying genetic determinants of drug response and discovering novel potent antimalarials. In support of these efforts, the parental lines and progeny of the 803xGB4 genetic cross were characterized by pharmaceutical compound screening and whole-genome sequencing (WGS). Results of the compound screen identified 52 highly-active compounds with potential for development as antimalarials. A confirmatory screen was performed to more accurately define parasite responses to 384 of the 2,816 compounds in the primary screen. Linkage analysis revealed 25 genetic loci significantly associated with parasite response to 61 compounds. A locus on chromosome 5 containing pfmdr1 was linked to response to six compounds, including the widely-used antimalarial mefloquine and the potential antimalarial triclosan. Progeny bearing the 803 allele at this locus were less sensitive to all six of these compounds. Results from RT-PCR experiments indicated increased transcription of pfmdr1 in 803 in the absence of copy number variation (CNV), implicating a possible promoter polymorphism. Analysis of WGS data suggested the presence of several possible CNVs, including a deletion of Rh2b in 803 inherited by a proportion of progeny, and a non-Mendelian amplification of Rh2a and Rh2b in three progeny. Results from PCR and RT-PCR experiments confirmed the deletion event, and indicated increased Rh2a and Rh2b transcript levels in one of the progeny with the amplification. High-throughput compound screening and WGS enable the discovery of parasite biological responses that have the potential to further malaria elimination efforts.